Rancang Bangun Solar Tracker Berbasis Arduino - Erman Al Hakim; Fahrudin, Bagus; Asni Tafrikhatin; Jati Sumarah (JASATEC : Journal Students Of Automotive, Electronic and Computer, 2022)
The use of sunlight as an alternative resource is starting to be widely applied. Sunlight can produce electrical energy using solar panels. In its installation, solar panels must get maximum sunlight. Static installation prevents solar panels from getting maximum sunlight at any given time. Installing a solar tracker to get maximum sunlight. This will increase the voltage generated by the solar panels. This research method uses the Research & Development method. This solar tracker uses Arduino Nano, LDR, voltage sensor, LCD, and servo motors. The LDR will catch sunlight which is then converted into a value and sent to Arduino Nano as a determinant of the direction of motion of the servo motor. Based on the test results, this product can increase the average output voltage of solar panels by 5.67%.